ACOUSTIC INFLUENCE MAP BASED FLAW SIZE IMAGING - LEPAGE, Benoit (2023)
Examples of the present subject matter provide techniques to accurately size flaws using acoustic inspection without expending significant computing resources and time. Examples described herein include techniques to convert amplitude-based inspection images, such as TFM or phased array ultrasonic testing (PAUT) images, into sizing images based on Acoustic Influence Maps (AIMs).